Konsumsi dan Kecernaan Protein Kasar (Crude Protein) Ransum Ternak Kambing yang diberi Pakan Hijauan dengan Suplemen By-Product Limbah Kulit Buah dan Biji Rambutan (Nephelium Lappaceum - Kadir, Muh. Jurhadi; Novieta, Intan Dwi (Fakultas MIPA UNM, 2019)
Abstract. This study aims to analyze the consumption and digestibility of crude protein fruit skin and rambutan seeds an animals feed suplements in goat rations fed forage. The study was conducted in Sidrap Regency and the Laboratory of Animal Feed chemistery, Fakulty of animal husbandry, Hasanuddin University in Makassar, using a Completely Randomized Design (RAL) with a 4 x 4 pattern (P0: 100 % forage (control), P1: 15 % fruit skin and 5 % seeds rambutan + 80 % forage, P2: 10 % fruit skin and 10 % seeds rambutan + 80 % forage and P3: 5 % fruit skin and 15 % rambutan seeds + 80 % forage), 4 adult goat. The data obtained were statistically analyzed using analysis of variance (ANOVA) and Duncan test, showing forage feeding with rambutan by-product supplements in the form of fruit skin and rambutan seeds as much as 20 % goat fodder had no significant effect (P>0.05) on the consumption of crude protein, and significant effect (P<0.05) on crude protein digestibility, Duncan’ test showed that there were significant differences (P<0.05) between each treatment. The study concluded that a good digestibility rate was obtained in P3 treatment, namely 5 % fruit skin and 15 % rambutan seeds + 80 % forage. It is recommended that further research be carried out to determine the level of feeding and changes in goat animal body weight. Keywords: rambutan skin and seeds, consumption, digestibility, goat.